(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
This paper focuses on Buber’s notion of an ’I-Thou’ relationship, and the mutuality within it where both client and therapist are touched and moved by each other as being central to therapist meeting client, and its relevance to existential therapy. This paper also explores bodily felt, nonverbal experience of being with client in informing the quality of the therapeutic relationship, which may be known implicitly at the sensory level, but may remain beyond full articulation.